Fabrication of YBa2Cu3O7−x (YBCO) superconductor bulk structures by extrusion freeforming. Issue 14 (1st November 2016) - Wei, Xiangxia; Nagarajan, Ragavendran Sundaram; Peng, Erwin; Xue, Junmin; Wang, John; Ding, Jun
Abstract: Practical applications of high temperature superconductors may require them to be processed into complex geometries. In this work, slurry-based extrusion freeforming coupled with high temperature treatment was attempted for the fabrication of bulk YBa2 Cu3 O7−x (YBCO) superconducting structures. YBCO parts with approximately 93% of the theoretical density were successfully fabricated after sintering at 940 °C for 60 h, with the obtained constituent phases strongly dependent on the heat treatment temperature and duration. A high critical transition temperature ( T C =92 K) and good magnetic levitation ability could be obtained after optimization of the heat treatment conditions. Overall, the experimental results demonstrate that extrusion freeforming is a feasible and effective technique for fabricating YBCO superconductors that have desirable configurations and good superconductivity properties.